GENETIC ASPECTS OF ACUTE POLYMORPHIC PSYCHOSIS (Academia Science Repository, 2023)
In this article, basic information about acute polymorphic psychoses, as well as genetic aspects of its manifestation in patients are sufficiently described. In addition, the article presents the factors that cause the disease using reliable sources.